2014
DOI: 10.1186/1471-2296-15-133
|View full text |Cite
|
Sign up to set email alerts
|

‘No need to worry’: an exploration of general practitioners’ reassuring strategies

Abstract: BackgroundIn view of the paucity of evidence regarding effective ways of reassuring worried patients, this study explored reassuring strategies that are considered useful by general practitioners (GPs).MethodsIn a study using a qualitative observational design, we re-analysed an existing dataset of fifteen stimulated recall interviews in which GPs elaborated on their communication with patients in two videotaped consultations. Additionally we held stimulated recall interviews with twelve GPs about two consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…GPs undertaking POCUS must be aware of this risk and communicate their medical reasoning to patients. However, providing reassurance for patients is both important and common in general practice [ 39 ] and GPs have been found to use diagnostic tests to reassure themselves and patients [ 35 , 40 ]. Measuring dimensions of reassurance immediately after the consultation, we found that patients felt an increased trust in their GP and a sense of security.…”
Section: Discussionmentioning
confidence: 99%
“…GPs undertaking POCUS must be aware of this risk and communicate their medical reasoning to patients. However, providing reassurance for patients is both important and common in general practice [ 39 ] and GPs have been found to use diagnostic tests to reassure themselves and patients [ 35 , 40 ]. Measuring dimensions of reassurance immediately after the consultation, we found that patients felt an increased trust in their GP and a sense of security.…”
Section: Discussionmentioning
confidence: 99%
“…Although sometimes done with good intentions, physicians should avoid premature reassurances (e.g., "It is not that bad…", "Everything is going to be fine") [21,22]. First, if patients' emotions are not addressed adequately, premature reassurance may be perceived by patients as not respecting their worries and fears.…”
Section: Discussion Of End-of-life Aspects With Patientswith Good Communication Skillsmentioning
confidence: 99%
“…Since evidence-based decision-making is often regarded as a normative issue, using the recordings might stop the professionals from giving socially acceptable answers instead of reflecting on their actual behaviour. In another project, we used videotaped consultations in interviews with experienced doctors to stimulate them to reflect on their reassuring behaviour [31]. The level of detail in the doctors’ reflections allowed us to uncover working mechanisms underlying the reassuring behaviour, guiding the reader to put this behaviour in context.…”
Section: How Reflective Vsi Can Elicit Tacit Knowledgementioning
confidence: 99%
“…Rather, they view the reflective interview as an opportunity (for interviewees) to ‘review events in which they have participated from an outsiders’ perspective but with an insider’s insight into their motivations and intentions’ [32]. The focus on reflection enables participants to construct meaning to behaviours applied unconsciously in practice [31], thus making the tool especially suited to uncover tacit theories, implicit ideas, and unspoken strategies behind learning and teaching in medical education.…”
Section: How Reflective Vsi Can Elicit Tacit Knowledgementioning
confidence: 99%
See 1 more Smart Citation